ANALYSIS DRIVING FACTORS OF BANKING CUSTOMERS TO CONDUCT THEIR DIGITAL TRANSACTIONS USING MOBILE BANKING - Fajar Satria; Asih Nuryanti (Jurnal Ekonomi, 2023)
The competition in banking industry is getting tighter and will be followed by a shift in public consumption towards digital which is driven by ease of use, transaction efficiency, economic value, product choices, promotion and discounts, to a secure payment system that underlies the trust factor for users. This study was conducted to analyze the relationship between variables adopted from TAM Theory and customer trust as a mediating variable to determine the factors that will be driving customers to make digital transactions using OCTO Mobile By CIMB Niaga. This study is a descriptive-quantitative method and illustrates the relationship between several variables supported by literature studies, some data that are included in the form of numbers on the results of the research conducted using data-collection techniques through questionnaires and interviews. The research results show that the driving factors for banking customers to carry out digital transactions using OCTO Mobile are customers with some curiosities about OCTO Mobile, trust with banking transaction services and ease of use facilities. Further research can involve service quality and customer experience to better represent the influence of service quality and customer experience on decisions and the sustainability of using Mobile Banking.  In the increasingly fierce competition in the financial sector, banking sector in Indonesia must be able to compete with competition landscape by taking customer trust into account the customer trust. This will aim to create customer usage intentions and loyalty. The strength features in digital banking will be useful for the achievement of companies to grow and compete themselves in the financial industry.